Preparation of benzyl isothiocyanate nanoemulsions by different emulsifiers: Stability and bioavailability. (December 2021) - Tian, Tian; Tong, Xiaohong; Yuan, Yue; Lyu, Bo; Jiang, Dengzhen; Cui, Wenyu; Cheng, Xiaoyi; Li, Liang; Li, Yang; Jiang, Lianzhou; Wang, Huan
Graphical abstract: Highlights: Emulsifier type affects the stability of nanoemulsion. Nanoemulsion systems can improve the bioavailability of bioactive components. Poor stability of nanoemulsion prepared by carbohydrate emulsifiers. The nanoemulsion constructed by SPI-PC has higher stability and bioavailability. Abstract: The stability and digestibility of food emulsions are affected by the various sources and structural characteristics of emulsifiers. Chitosan, Arabia gum, soy protein isolate (SPI), and soybean protein isolate-phosphatidylcholine (SPI-PC) were used as natural emulsifiers in this study, and a 10 % (v/v) MCT oil phase (containing 10 methyl g/mL benzyl isothiocyanate (BITC)) was used for the preparation of oil in water nanoemulsions. The stability of nanoemulsions and their in vitro digestion characteristics were determined using dynamic light scattering, scanning electron microscopy, differential scanning calorimetry, and ultraviolet-visible spectrophotometry. The average particle size and potential of chitosan and Arabia gum nanoemulsion changed significantly under extreme environmental conditions, and their stability was poor. SPI-PC nanoemulsion exhibited a more stable transport system. The type of emulsifier has a significant effect on the release of free fatty acids and BITC digestibility. SPI-PC nanoemulsion have higher BITC bioavailability when compared to other emulsifiers. The results showed that natural emulsifiers could stabilize the emulsion, but there was a significant difference in their stability. The SPI-PC composite emulsifier could produce a nanoemulsion that is relatively stable, safe, and high in bioavailability.